Exploring generation z’s fascination with Jakarta art museum through social media contents - Muhammad Hafiz Nurul Haqqi; Harjanto, Rudy (Faculty of Communications Science, Dr. Soetomo University, 2025)
Abstract This study explored how museums can optimise their social media strategies to engage Generation Z. This tech-savvy demographic values interactive, visually appealing, and immersive online experiences by examining the case of Art:1 New Museum in Jakarta. This research investigated strategies cultural institutions can adopt to align with Generation Z's digital habits and preferences. Rooted in the AISAS model (Attention, Interest, Search, Action, and Share), this study examined the role of social media in shaping brand image, online reputation, and visitor engagement by employing a qualitative approach, and data were collected through in-depth interviews with a museum gallery manager, regular visitors, the artist and competitor along with content analysis of Art:1’s Instagram account. The findings reveal that Art:1’s limited use of interactive features, inconsistent content quality, and lack of user-generated content engagement reduce its appeal to younger audiences. Despite its strong offline reputation among art collectors, Art:1 struggles to establish a cohesive digital presence that resonates with Generation Z. This study offers actionable recommendations, including enhancing content quality, integrating interactive features, fostering user-generated content, and aligning digital strategies with the preferences of younger audiences. These findings provide valuable insights for cultural institutions seeking to remain relevant in the digital era by adapting their marketing strategies to better meet emerging demographics' needs.